Mood Management : a Cognitive-behavioral Skills-building Program for Adolescents. - Langelier, Dr. Carol A. A. (SAGE Publications, 2001)
Written at a level that is easy for adolescents to understand, this illustrated skills workbook features exercises and checklists for participants to use as they work through the Mood Management program.